Analysis of Productivity Measurement in CPO Production Using OMAX Method - sakti, Ade Dwi; Hartati , Misra; Nur , Muhammad; Harpito, Harpito (Spektrum Industri, 2023)
The primary focus of this research revolves around the measurement of productivity and the factors that impact Crude Palm Oil (CPO) production which currently faces challenges in assessing whether existing productivity falls into the 'satisfactory' category. The contribution of this study is conducting a comprehensive productivity assessment, focusing on metrics and identifying the causes of productivity decline, especially potential points of failure. The measurement indicators use the Objective Matrix (OMAX) method which includes five ratios, including raw material utilization, energy consumption, labor efficiency, optimization of production targets, and production capacity utilization. The Analytical Hierarchy Process (AHP) is used to assign relative weight to factors that contribute to overall productivity. In addition, Failure Modes and Effects Analysis (FMEA) functions as a tool to determine the causes of decreased productivity by considering the potential for failure to occur. The research results show that productivity reached its highest point in March at 219.93% and the lowest in July at -67.33%. Based on the score assessment, this decline was mainly caused by the lack of optimal achievement of production targets, symbolized by a ratio of 4 to a score of 45. Potential causes for this ratio include non-compliance in selecting FFB that meets standards, and production standards that are too ambitious. targets, and mental and physical fatigue and stress. To improve overall performance, proposed improvements include the application of Internet of Things (IoT) technology, such as the use of sensors and automation systems in production processes, as well as investment in agricultural technology as a monitoring system. This increase is aimed at achieving higher production targets and overall efficiency.